Perancangan Alat Praktikum Fisika Gerak Jatuh Bebas Berbasis Internet of Things - Agustian, Anildo; Anas, Adian Aristia; Wilza, Romi; Junaidi, Ahmad (Politeknik Negeri Sriwijaya, Indonesia, 2024)
Kinematics of Free Fall Motion (FFM) is one of the important chpaters in physics courses. However, the Physics Laboratory at the Department of Mechanical Engineering, State Polytechnic of Sriwijaya does not have practical tools of FFM yet. This study aims to design and determine the performance of the FFM physics lab based on the Internet of Things (IoT). This research method uses qualitative method and experimental approach. This physics lab is afterward compared to theoretical calculations from the FFM formula by testing it at 3 falling heights of 100 cm, 130 cm, and 150 cm, as well as at 3 different masses of 100 g, 200 g, and 500 g. All data collected need to be analyzed using ANOVA of linear regression to obtain the level of accuracy and the relationship between falling heights and masses towards final velocities of the test objects. The results of the study shows that the development of the lab physics FFM IoT-based has very decent performance as long as the average error percentage is 5.52% or less than 10% as well as the level of average accuracy level is 94.48%. The results of the analysis showed that falling heights have a significant effect towards final velocities of the FFM’s test objects. On the other hand, variety of masses barely has no effect towards final velocities of the physics lab.